The XIIIth Banff Conference on Allograft Pathology: The Banff 2015 Heart Meeting Report: Improving Antibody‐Mediated Rejection Diagnostics: Strengths, Unmet Needs, and Future Directions. Issue 1 (12th December 2016) - Bruneval, P.; Angelini, A.; Miller, D.; Potena, L.; Loupy, A.; Zeevi, A.; Reed, E. F.; Dragun, D.; Reinsmoen, N.; Smith, R. N.; West, L.; Tebutt, S.; et al.
Abstract : The 13th Banff Conference on Allograft Pathology was held in Vancouver, British Columbia, Canada from October 5 to 10, 2015. The cardiac session was devoted to current diagnostic issues in heart transplantation with a focus on antibody‐mediated rejection (AMR) and small vessel arteriopathy. Specific topics included the strengths and limitations of the current rejection grading system, the central role of microvascular injury in AMR and approaches to semiquantitative assessment of histopathologic and immunophenotypic indicators, the role of AMR in the development of cardiac allograft vasculopathy, the important role of serologic antibody detection in the management of transplant recipients, and the potential application of new molecular approaches to the elucidation of the pathophysiology of AMR and potential for improving the current diagnostic system. Herein we summarize the key points from the presentations, the comprehensive, open and wide‐ranging multidisciplinary discussion that was generated, and considerations for future endeavors. Abstract : This article summarizes the Banff conference on heart transplantation with a focus on antibody‐mediated rejection, strengths and limitations of the current rejection grading system, the important role of serologic antibody detection and the potential application of new molecular approaches to the elucidation of the pathophysiology of antibody‐mediated rejection, and the potential for improving the current diagnostic system. See the companion report onpage 28 .